The Effects of NAFTA/CUSFTA on Agricultural Trade Flows: An Empirical Investigation. (4th October 2016) - Ghazalian, Pascal L.
Abstract : This paper examines the effects of the North American Free Trade Agreement (NAFTA) and its predecessor, the Canada‐United States Free Trade Agreement (CUSFTA), on agricultural trade flows at disaggregated product categories. The empirical analysis is implemented through gravity models using different econometric methods. It accounts for the baseline NAFTA/CUSFTA‐unrelated magnitudes of trade between member countries throughout the assessment of the NAFTA/CUSFTA trade effects. The benchmark estimates show considerable differences across agricultural product categories. The net post‐NAFTA/CUSFTA magnitudes of trade between member countries are found to be markedly low in some cases, underlining missed regional trade opportunities. The empirical analysis proceeds to estimate the NAFTA/CUSFTA trade effects by time period and by bilateral trading partnership, revealing important variations. Cet article examine les effets de l'Accord de Libre‐Échange Nord‐Américain (ALÉNA) et de son prédécesseur, l'Accord de Libre‐Échange entre le Canada et les États‐Unis (ALÉCÉU), sur les flux commerciaux agricoles au niveau des catégories ventilées. L'analyse empirique est mise en œuvre grâce à des modèles de gravité en utilisant une variété de méthodes économétriques. Elle compte pour la ligne de base des magnitudes non‐reliées à l'ALÉNA/ALÉCÉU du commerce entre les pays membres à travers l′évaluation des effets de l'ALÉNA/ALÉCÉU sur le commerce. Les estimations de référence montrent des différences considérables entre les catégories de produits agricoles. Les magnitudes post‐ALÉNA/ALÉCÉU nettes du commerce entre les pays membres se trouvent d′être considérablement faibles dans certains cas. Ces résultats soulignent des opportunités commerciales régionales manquées. L'analyse empirique procède à estimer les effets de l'ALÉNA/ALÉCÉU sur le commerce par période et par partenariat commercial bilatéral, et elle montre des variations importantes.